The influence of ants on the insect fauna of broad-leaved, savanna trees - Grant, Susan (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 1985)
The influence of foraging ants on the insect fauna within the canopy of the tree species Terminalia sericea, Burkea africana and Ochna pulchra was studied in an area of typical South African savanna, over a two year period. The number of individual insects and their species composition was compared on unbanded, ant-infested plants and on banded plants where ants had been excluded. Differences in the level of herbivory recorded on banded and unbanded trees were related to the guild composition of insects within the canopy, and the results are discussed in terms of plant protection as a consequence of ant - insect interactions. Twenty-six ant species were recorded on the study trees at Nylsvley, with individuals belonging to the genus Crematogaster being numerically abundant and dominant within the canopy of each species of tree. These dominant ant species influenced the insect fauna by their strong dependence on honeydew, encouraging a build up in numbers of Homoptera on the branches and leaves of foraged trees, and supporting homopterous populations within the confines of their nest compartments . The exclusion of ants from trees led to fewer "mobile" homopterans (Aphididae, Membracidae, Psyllidae and Cicadellidae) and "sessile" homopterans (mainly Coccidae but also Pseudococcidae). Pyrethrum spraying showed that the guild composition of non-homopterous insects was similar on banded and unbanded trees. Differences in the level of herbivory on banded and unbanded trees suggested that, although slight, foraged trees were protected from some damage by the presence of ant species within the canopy. A trend did exist towards a greater number of insect individuals and species on unbanded trees, and it is postulated that during the period 1982 1984 when drought conditions prevailed over Nylsvley, ants do not reduce insect numbers through predation or disturbance but simply deter phyllophagous feeding. A separate experiment showed that Crematogaster constructor would feed on the eggs and early instar larvae of the saturnid moth, Cirina forda, but low numbers of lepidopterous larvae on the trees may have forced ants to seek honeydew. The negative impact of large homopterous populations on foraged trees was only seen in an isolated field observation where Polyrachis schistacea was found to associate with the lac insect Tachardina sp . . In conclusion it can be said that where homopterans are not the dominant phyllophages, plants do benefit from foraging populations of ants in that damage to the leaves is reduced.
Keywords: Ants -- Behavior; Insects -- Host plants